Non-medical Use of Prescription Stimulants Among College Students: Non-oral Routes of Administration, Risk Factors, Motivations, and Pathways - Butler, Stephen F.; Faraone, Stephen V.; Rostain, Anthony L.; Newcorn, Jeffrey H.; Antshel, Kevin M.; Robbins, Rebekkah S.; Green, Jody L. (Frontiers in Psychiatry, 2021)
Introduction: Non-medical use (NMU) of prescription stimulant medications is a continuing public health concern. Stimulant medications prescribed for attention-deficit/hyperactivity disorder (ADHD) are widely available on college campuses, and, as a consequence, college students may have multiple opportunities to engage in prescription stimulant NMU. This online self-report survey examined prescription stimulant NMU among college students, including: (1) patterns of non-oral route of administration (ROA); (2) motivations for non-oral ROAs; and (3) retrospectively recalled pathways of initiation. Method: The survey sample was created from a pool of 3,379 respondents, who were matched to a sampling frame constructed from the 18–26-year-old, college student sample of the 2016 American Community Survey (ACS). About 14% (n = 486) from the overall pool were identified as college students with self-reported prescription stimulant NMU, all of whom completed the survey. The survey covered user characteristics, prescription and illicit substance use, age of first NMU, motivations for NMU, sources of procurement, and ROAs used. Results: Among 486 students reporting prescription stimulant NMU, 43% had a lifetime diagnosis of ADHD. More than 90% reported polysubstance use, with 55% using illicit substances other than marijuana. Slightly more than 2 in 5 (43.3%) reported using illicit substances prior to prescription stimulant NMU, 24.6% used both at the same age, and 32.0% engaged in NMU of prescription stimulants prior to using illicit substances. Prescription stimulant NMU preceded prescription opioid NMU 45% of the time. More than a quarter of those engaged in prescription stimulant NMU (27.9%) initiated prescription stimulants alone or at the same age as other drugs. Most prescription stimulant NMU was oral, however 23.0% reported any non-oral use: snorting (20.4%), smoking (6.0%)and/or injection (3.5%). Non-oral use was associated with being male, obtaining medication from a dealer, use to get high, and/or a substance use disorder diagnosis. Conclusions: Prescription stimulant NMU often occurs in the larger context of other substance use among college students. Injection, an under-researched route for prescription stimulants, was associated with male gender, history of substance use and higher likelihood of illicit substance use. Nearly a quarter of college student survey respondents reported use with non-oral routes, which is associated with other high-risk behaviors. Efforts to reduce non-oral prescription stimulant NMU in college students are warranted.